Post‑pandemic predictors of nurse burnout: a structural equation modeling analysis - Antonius Ngadiran; Roselina Tambunan (Universitas Aisyiyah Yogyakarta, 2026)
Occupational burnout is a major concern among nurses because it can affect both staff well-being and patient safety. This study aimed to identify the dominant factors driving burnout-focusing on personal characteristics, work environment, locus of control (LoC), and work experience among hospital nurses in the post-pandemic landscape. A cross-sectional study was conducted with 431 nurses at 2024, and data were analyzed using Structural Equation Modeling. Most respondents were aged 23–35 years, had professional education, and had worked for more than five years. The analysis showed that respondent characteristics were significantly associated with lower burnout levels (β = -0.334; p < 0.001), as was a supportive work environment (β = -0.186; p < 0.001). In contrast, locus of control was not significantly associated with burnout (β = 0.065; p = 0.368). Longer professional tenure was associated with higher burnout (β = 0.132; p = 0.007). The multivariate analysis confirm that the combination of characteristics, work environment, LoC, and work experience explained 10.9% of the variation in burnout. Among the personal factors, age (loading 0.838) and marital status (loading 0.800) were the strongest predictors. In the work environment construct, both physical (loading 0.891) and non-physical conditions (loading 0.919) were important contributors to professional exhaustion. These findings underscore the need for institutional strategies that prioritize environmental support and address the long-term stress associated with nursing service to reduce burnout and sustain care quality. Future research should examine workload, staffing ratio, compensation, leadership, shifts, and social support.